To solve the system, we can do it by substitution, which is following the procedure below.
0. Isolating ,x ,from the second equation.
![x=-7+y](https://img.qammunity.org/2023/formulas/mathematics/college/fy0rv5bu8ltly04ytlem9lp6txz2ah0599.png)
2. Replacing the isolated expression of x in the first equation.
![-4\cdot(-7+y)+3y=23](https://img.qammunity.org/2023/formulas/mathematics/college/bxtfw60722qp702utd4fyrctqm7t1xgaae.png)
![28-4y+3y=23](https://img.qammunity.org/2023/formulas/mathematics/college/is5c3m6901j4c45haxfuq82viifja127d1.png)
4. Solving for y.
![4y-3y=28-23](https://img.qammunity.org/2023/formulas/mathematics/college/25owd068pxgssfisvybcm43aa1ht0p17mf.png)
![y=5](https://img.qammunity.org/2023/formulas/mathematics/high-school/movw1ono7jyn4ydkf704zanhycsr2mjdby.png)
5. Replacing the value of y in the isolated expression of x.
![x=-7+5](https://img.qammunity.org/2023/formulas/mathematics/college/2tch9vh3s3ivtm708bp2laelf5k9vcktx7.png)
![x=-2](https://img.qammunity.org/2023/formulas/mathematics/college/hgapxsmy5hypkh6t7zmgcc8cu0ivm02dxk.png)
Answer: x = -2; y = 5.